Asymptomatic Osteoblastoma of the Mandible: A Rare Case Report - Soudabeh Sargolzaei; Saede Atarbashi-Moghadam; Fatemeh Latifi (Mashhad University of Medical Sciences, 2018)
Osteoblastoma is a rare solitary osteoblastic bone neoplasm. It is characterized by proliferation of osteoblasts forming trabeculae within a vascular fibrous stroma. There is a variety of jaw bone lesions with very close clinical, radiological and microscopic interrelations, which make diagnosis more challenging. Familiarity with these rare bony lesions is vital for oral pathologists. This report presents a new case of asymptomatic mandibular osteoblastoma occurring in a 43-year-old male